ZnO Nanowire Networks as Photoanode Model Systems for Photoelectrochemical Applications - Liana Movsesyan (Nanomaterials, 2018)
In this work, the fabrication of zinc oxide (ZnO) nanowire networks is presented. By combining ion-track technology, electrochemical deposition, and atomic layer deposition, hierarchical and self-supporting three-dimensional (3D) networks of pure ZnO- and TiO2-coated ZnO nanowires were synthesized. Analysis by means of high-resolution transmission electron microscopy revealed a highly crystalline structure of the electrodeposited ZnO wires and the anatase phase of the TiO2 coating. In photoelectrochemical measurements, the ZnO and ZnO/TiO2 nanowire networks, used as anodes, generated higher photocurrents compared to those produced by their film counterparts. The ZnO/TiO2 nanowire network exhibited the highest photocurrents. However, the protection by the TiO2 coatings against chemical corrosion still needs improvement. The one-dimensionality of the nanowires and the large electrolyte-accessible area make these 3D networks promising photoelectrodes, due to the improved transport properties of photogenerated charge carriers and faster redox reactions at the surface. Moreover, they can find further applications in e.g., sensing, catalytical, and piezoelectric devices.